Difference in Effects of Listening to The Al-Quran and Music on Sensibility - Ahmad Rusdi; Fani Eka Nurtjahjo; Sakinah Sakinah (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Sensitivity is a measure that can reflect the balance of human affection. Therefore, this study aims to determine difference in the effects of listening to the Al-Quran and music on sensibility. A quasi-experimental method was used by forming 2 groups of participants, each consisting of 4 individuals. The first group listened to music, while the second listened to the Al-Quran and read the translation. Participants were placed in an isolation room to take part in the experimental process. Sensibility was then measured with Sensirec before the treatment was given. In the music treatment group, instrumental music with the title Pachelbel Major in D was played. Meanwhile, in the other group, the participants were asked to listen to the Al-Quran and read the translation of Surah al-Insān. After treatment, sensibility was measured again using Sensirec, and an attention check questionnaire was filled out. The results showed that the effects of decreasing arousal (deactivation) were stronger and more significant in the Al Quran group (η2=.833; p=.034), compared to the music group (η2=.183; p=.183). Low arousal positive affect showed feelings of calm, relaxation, and satisfaction. In addition, the situation could predict the well-being, mental health, and life satisfaction of the participants. Based on these results, the technique of listening to the Al-Quran could be developed as a more systematic part of Islamic psychotherapy.